Thermal behaviour of concrete walls for hot climate region instead of common bricks - Ali Hassan, Atif (Iraqi Journal of Civil Engineering, 2013)
To reduce using the brick as a unloaded walls in frame building by using concrete parts to preproduction walls and is assemble in working area , the suggested wall is consist of a double parts (1000x500x140)mm with 50mm insulating material and arrangement parts by roller bolts with building frame and covered by sheets as external finishing material, and used a gypsum layer of 3mm thickness as an internal finishing material, therefore, the total wall thickness is 200mm. The thermal behavior of that suggested wall was measured for 15 hour/day for one day in July month. in Baghdad climate region (33.2 N°). The researcher found that, the metal sheet which paint with thermal & plastic paints cover that suggestive wall is gave more energy saving when it compared with brick wall (240mm,120mm) and the saving value was increased when uses reeds stalks sheay 50mm (thickness) as an insulating material among the concrete wall instead of air gap.